“It is to be a punishment or a pardon is granted” or Whether the Criminal Code of Ukraine needs to have incentive norms about the crimes against human freedom, honor and dignity - Ya. H. Lyzohub (Law and Safety)
The paper is focused on the analysis of the stimulatory norms expediency in the criminal law of Ukraine. The objective of the paper is to reveal the significance of legal encouraging of an offender to stop his further criminal activity. Especially, it is necessary in conditions of Ukraine’s movement from a previous Soviet heritage to modern punishment standards, where criminal liability is not only punishment, but it is also a strategy to prevent a crime.